Play Therapy Bermuatan Permainam Tradisional untuk Melatih Kemampuan Interaksi Sosial Anak Autis - Henny Indreswari; Achmad Miftachul 'Ilmi; Khairul Bariyyah (JKI (Jurnal Konseling Indonesia), 2022)
This study discusses the appropriate psychological intervention for children with Asperger's disorder who experience difficulties in social interaction. The purpose of this study is to provide a description of the characteristics of children with autism and their social interactions, to describe the concept of play therapy with traditional games to train social interaction in children with autism and to provide recommendations for the design of implementing play therapy with traditional games to train social interaction in children with autism. The research method used is a literature review with five stages of literature collection, literature selection, literature evaluation, conclusion drawing, and discussion of the study results with 10 relevant articles. Based on a literature review, it was found that appropriate age for providing intervention for children with autism-related to their social interaction ability is 5-12 years old and play therapy with traditional games is a suitable intervention. Traditional game media that can be used include sobak sodor, engklek, bentengan, cublak suweng, and ular naga. Implementation of play therapy with traditional games can use the single subject design A-B-A research method. The purpose of this research is to contribute to field of behavior modification that can be used by teachers, therapists, and counselors in helping children with autism develop their ability to interact with their environment.